Factors affecting generation Y consumers’ purchase intention towards organic products in Malaysia - Chong, Jia Ying; Chua, Hian Soon; Lwee, Kui Fang; Ng, Shih Yean (2017)
The primary objective of this research is to examine the factors that impact Generation Y consumers’ purchase intention towards organic products in Malaysia. This research is to investigate the relationship of health concerns, environmental concerns, perceived value, availability towards consumer attitudes, the relationship between consumer attitudes and purchase intention and to test the role of consumer attitudes as a mediator between availability and purchase intention. The research was carried out as a causal research and the information required for this research were obtained via self-administered questionnaire. Statistical Package for Social Sciences (SPSS) version 17.0 was used to analyse the data obtained from the questionnaire. There were 300 responses that were collected and the data have been analysed and interpreted using descriptive analyses, inferential analyses and mediator analysis. All six hypotheses were supported based on the results of the analyses. This study is particularly useful for organic marketers and practitioners in Malaysia as Generation Y consumers are considered to be the largest and wealthiest group of consumers in the country. The implications of this study, its limitation and recommendations for future researches were included in the concluding chapter to serve as a guide to the relevant stakeholders.